Relationship between Work Environment and Employee Performance among Public Servants Attending Senior Management Course in Kenya - Kimotho, Susan; Okello, Osoo (International Journal of Psychology, 2025)
Purpose: The aim of this study was to establish the relationship between work environment and work performance of employees in public service in Kenya. This was necessitated by the numerous challenges faced by public servants amidst the budgetary constraints and increased taxes making the work environment laced with high stress levels that are either work-related or personal. The study therefore sort to determine the factors within the work environment and how they influence an employee’s work performance. Methodology: The research design adapted was use of cross-sectional research survey, the target population was Public Servants represented by KSG Senior Management Course class 409/2023. The sample was 76 of the 112 public servants in the SMC 409/2023 class selected through simple random sampling. Data was collected using structured questionnaires, data analysis done descriptively and inferentially using Microsoft Excel and SPSS version 27. The results were presented through use of pie charts and tables. Findings: 96.1% percent of the respondents believed that the work environment positively affected their job performance, which is 72 respondents, while 1.3% believed that it does not, which is only one respondent. Two respondents were unsure if the work environment affects their job performance. In the measurement of the extent of the work environment influencing their performance, 59.7% of them (46) agreed that it has very strong effects. 24.7% (19) respondents believed that work environment has a strong impact on their performance, 7.8% were not sure if it has or doesn't, 5.2% (4) respondents disagreed that each has an effect on the performance, while two people strongly disagreed if it has which is 2.6 percent. 46.8%, that is 36 people, were satisfied with their current work environment. 6.5%, which is five people, were very satisfied with their current work environment. 23.4%, 18 respondents, were neither satisfied nor dissatisfied with their current work environment, 16.7% (13) respondents were dissatisfied with their current work environment, and 5, 6.5%, were very dissatisfied with their current work environment. Unique contribution to Theory, Practice and Policy: This study findings were important for theory because they brought forth new information about the levels of work performance among public servants. For practice, the study will guide on measures that can be done as recommendations to improve work performance and In Policy, the public service can utilize data from this study to improve on their work place policies to inculcate the unique needs of public servants thus hoping implementation will promote work performance.